Pain and other non‐neurological adverse events in children with sickle cell anemia and previous stroke who received hydroxyurea and phlebotomy or chronic transfusions and chelation: Results from the SWiTCH clinical trial. Issue 11 (30th August 2013) - Alvarez, Ofelia; Yovetich, Nancy A.; Scott, J. Paul; Owen, William; Miller, Scott T.; Schultz, William; Lockhart, Alexandre; Aygun, Banu; Flanagan, Jonathan; Bonner, Melanie; Mueller, Brigitta U.; Ware, Russell E.; et al.
<x xml:space="preserve">Abstract</x> To compare the non‐neurological events in children with sickle cell anemia (SCA) and previous stroke enrolled in SWiTCH. The NHLBI‐sponsored Phase III multicenter randomized clinical trial stroke with transfusions changing to hydroxyurea (SWiTCH) (ClinicalTrials.gov NCT00122980) compared continuation of chronic blood transfusion/iron chelation to switching to hydroxyurea/phlebotomy for secondary stroke prevention and management of iron overload. All randomized children were included in the analysis (intention to treat). The Fisher's Exact test was used to compare the frequency of subjects who experienced at least one SCA‐related adverse event (AE) or serious adverse event (SAE) in each arm and to compare event rates. One hundred and thirty three subjects, mean age 13 ± 3.9 years (range 5.2–19.0 years) and mean time of 7 years on chronic transfusion at study entry, were randomized and treated. Numbers of subjects experiencing non‐neurological AEs were similar in the two treatment arms, including SCA‐related events, SCA pain events, and low rates of acute chest syndrome and infection. However, fewer children continuing transfusion/chelation experienced SAEs (P = 0.012), SCA‐related SAEs (P = 0.003), and SCA pain SAEs (P = 0.016) as compared to children on the hydroxyurea/phlebotomy arm. The timing of phlebotomy did not influence SAEs. Older age at baseline predicted having at least 1 SCA pain event. Patients with recurrent neurological events during SWiTCH were not more likely to experience pain. In children with SCA and prior stroke, monthly transfusions and daily iron chelation provided superior protection against acute vaso‐occlusive pain SAEs when compared to hydroxyurea and monthly phlebotomy. Am. J. Heamtol. 88:932–938, 2013. © 2013 Wiley Periodicals, Inc.